Improving Studentsâ Speaking Skill through Pyramid Discussion: A Classroom Action Research at the Tenth Grade Students of the Senior High School in Kendawangan - ., Sulistamawati (West Kalimantan Scholars: Studies on English Language and Education, 2015)
The purpose of the classroom action research was to find out the improvement of the studentsâ speaking skill after applying pyramid discussion at the tenth grade students of the senior high school in Kendawangan. The participants were 24 students at the tenth grade students of a senior high school in Kendawangan. Observation and measurement were used as the techniques for data collection.